KORELASI AKTIVITAS BELAJAR SISWA DI RUMAH DENGAN HASIL BELAJAR SISWA KELAS II SEKOLAH DASAR - Mila Karmila; Budiman Tampubolon; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the correlation between student learning activities while studying at home during the covid – 19 pandemic and the learning outcomes of grade II students at Public Elementary School 28 North Pontianak. Descriptive method with the form of interrelationship studies using correlation studies. Population study with a total of 30 student’s. Data collection techniques in this research are indirect communication and documentary studies. The data collection tools used were questionnaires and documents on the average value of report cards. The results showed that 71.13% of student’s learning activities while studying at home during the covid – 19 pandemic were in the "enough" category. While student learning outcomes on the overall average report card score of 81.94. Based on the results of statistical calculation’s using the product moment correlation formula for calculating student learning activities with student learning outcomes, the r count is 0.660, while the r table is 0.361 meaning r count > r table. Based on the results of the research, the relationship between student learning activities while studying at home during the covid – 19 pandemic and the learning outcomes of grade II student’s at Public Elementary School 28 North Pontianak is in a strong correlation. Keyword’s : Correlation, Learning Activities, and Learning Outcomes.